The choice of district road construction by the method of analytical hierarchy process and simple multi attribute rating technique - Widyaningsih, Nunung; Purwoko Kusumo Bintoro, Bambang; Purwoko Kusumo Bintoro, Bambang; Hidayat Renggah, Rahmat; Hidayat Renggah, Rahmat (International Journal of Engineering and Technology, 2018)
The choice of country road construction applying the method of Analytic Hierarchy Process and Simple Multi Attribute Rating Technique for the aim of the formulation and decision-making for the choice of road construction between flexible pavement and rigid pavement. The case study takes a road in the area of Poso, Center of Sulawesi, Indonesia. Data is taken by using a detailed questionnaire and distributed to respondents at random by 30 people. From the analysis of the obtained results are as follows as the selection of the path using the method of Analytic Hierarchy Process by weighting variables long-term durability and maintenance, the Simple Multi Attribute Rating Technique method by trading and cost benefit. Based on long-term durability, road construction should be resistant to weather is the first priority, and to resistant of traffic density and the road construction must be impervious to the ground shifting. Based on maintenance. The first priority is the path should be a period of excellent treatment and ease implemented of construction. Road construction to be used based on Analytic Hierarchy Process and Simple Multi Attribute Rating Technique is the flexible pavement. The weighting of the results seen from long-term durability and maintenance are obtained that the road asphalt has the highest weight value is 61.4% while the concrete path is 38.6%. The cost of the flexible pavement has a price of Rp. 365.788.000,-value benefit of/km is 61.40%, whereas for rigid path have a price amounting is Rp. 708.029.000,-value benefit of/km is 38.60%.Â Â